Comparative proton and photon treatment plans in children treated for neuroblastoma - Anna Embring; Ingrid Kristensen; Martin P. Nilsson; Jacob Engellau; Malin Blomstrand; Charlotta Fröjd; Måns Agrup; Anna Flejmer; Anna-Maja Svärd; Anna Asklid (Acta Oncologica)
Background and purpose: Neuroblastoma is the most common extracranial solid tumour in children. Radiotherapy is commonly part of the multimodal treatment for high-risk patients. The aim of this study is to analyse doses to organs at risk (OAR) in comparative proton and photon treatment plans for children treated for neuroblastoma and report side effects.